Clinical feasibility study of transcatheter edge-to-edge mitral valve repair in dogs with the canine V-Clamp device - Potter, Brianna M.; Orton, E. Christopher; Scansen, Brian A.; Abbott-Johnson, Katie M.; Visser, Lance C.; Chi, I-Jung B.; Ross, Evan S.; Del Nero, Bruna; Tantisuwat, Lalida; Krause, Ellen T.; Rezende, Marlis L.; Mama, Khursheed (Frontiers in Veterinary Science, 2024)
ObjectiveTo determine procedural feasibility, safety, and short-term efficacy in dogs with severe degenerative mitral regurgitation (MR) undergoing transcatheter edge-to-edge repair (TEER) with a canine-specific device.DesignProspective, single-arm (uncontrolled), single-institution clinical feasibility study.AnimalsFifty client-owned dogs with severe degenerative MR operated over a 28-month period.MethodsTEER was performed using the canine mitral V-Clamp via a transapical approach using transesophageal echocardiographic and fluoroscopic guidance. Indices of MR severity were determined by echocardiography the day before and 2 to 3 days after the procedure.ResultsProcedural feasibility was 96% based on delivery of at least one device in 48 of 50 dogs. There were no procedural deaths. Procedural safety was 96% based on survival to hospital discharge in 48 of 50 dogs. Euthanasia in 2 dogs prior to hospital discharge was due to damage of the mitral valve and worsened MR after the procedure. Device-related adverse event rate was 6.3% based on 3 events (single-leaflet device detachment, locking failure, locking failure with device embolization) in 59 implanted devices. All three events were nonfatal and successfully treated with a second device. Median regurgitant volume (mL/kg) decreased (p < 0.001) from 2.3 [1.9, 3.1] to 1.1 [0.3, 1.8]. Median effective regurgitant orifice area (cm2/m2) decreased (p < 0.001) from 0.60 [0.40, 0.80] to 0.25 [0.10, 0.50].Conclusion and clinical importanceInitial feasibility results support continued development of TEER as a procedurally feasible, relatively low-risk, and low morbidity treatment for degenerative MR in dogs. Operator experience and case selection are likely to be important components of success of this technique. Evidence of short-term efficacy is promising but needs to be verified with longer-term follow up.